Effects of Local and Systemic Zoledronic Acid Application on Titanium Implant Osseointegration: An Experimental Study Conducted on Two Surface Types - Dundar, Serkan; Yaman, Ferhan; Gecor, Orhan; Cakmak, Omer; Kirtay, Mustafa; Yildirim, Tuba Talo; Benlidayi, Mehmet Emre (Lippincott Williams & Wilkins, 2017)
The aim of this study was to evaluate the effects of local and systemic zoledronic acid (ZA) applications on titaniumoksit ceramic blasted (TiO-CB)- and sandblasted large acid-grit (SLA)-surfaced titanium implant osseointegration. Twelve New Zealand White rabbits were used in the study, divided into 6 groups: the TiO-CB (TiO-CB-CNT) (n = 2) and SLA (SLA-CNT) (n = 2) control groups in which TiO-CB- and SLA-surfaced titanium implants were surgically inserted into rabbit tibias but no treatment was applied; the TiO-CB (TiO-CB-LZA) (n = 2) and SLA (SLA-LZA) (n = 2) local ZA groups in which 1 mL of normal saline solution containing 2 mg of ZA was injected into sockets and after this the implants were integrated; and the TiO-CB (TiO-CB-SZA) (n = 2) and SLA (SLA-SZA) (n = 2) systemic ZA groups in which a single infusion of 0.1 mg/kg of ZA was administered during surgical implant insertion. Following a period of osseointegration, bone implant contact (BIC) was recorded as a proportion of the total implant surface length in direct contact with the bone. Results of this study indicate that BIC was greater in the systemic ZA application groups than in the local ZA application groups, and BIC was greater in the local ZA groups than in the controls. Statistically significant differences in BIC were not detected between the TiO-CB- and SLA-surfaced implants in all the groups. Furthermore, this study did not reveal significant differences between the 2 types of surfaces due to similar average roughness values. Overall, systemic ZA application was found to be more effective in increasing BIC than local ZA application based on the results obtained by testing 2 implant surfaces.
Keywords: Bone implant connection; osseointegration; rabbit tibiae; surface roughing; zoledronic acid